Sunscreen Cream Formulation from Green Tea Extract (Camellia sinensis) and SPF Value Test - Putri, Maidina; Hariati, Andi; Basir, Anastasia A. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Green tea (Camellia sinensis) is known to contain polyphenol compounds, especially catechins, which act as antioxidants and photoprotectors against ultraviolet (UV) radiation. This study aims to formulate a sunscreen cream from green tea extract and test its Sun Protection Factor (SPF) value in vitro using a UV-Vis spectrophotometer. The research methods include green tea leaf extraction by 70% ethanol maceration, cream formulation in three extract concentrations (5%, 10%, and 15%), and SPF testing using the Mansur method. The results showed that increasing the concentration of green tea extract was directly proportional to the increase in SPF value, where a concentration of 15% had an SPF value of 27.4 which is classified as very high protection. The cream formulation also met the organoleptic, pH, homogeneity, and stability test parameters. In conclusion, green tea extract can be formulated into an effective sunscreen cream with a high SPF value.